2011
DOI: 10.1002/pen.21938
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene terephthalate)/carbon nanotube composites prepared with chemically treated carbon nanotubes

Abstract: Surfaces of multiwalled carbon nanotubes (CNT) were functionalized by treatment with strong acid mixture (purification) followed by modification with sodium dodecyl sulfate, poly(ethylene glycol) (PEG), and diglycidyl ether of Bisphenol A (DGEBA). Poly(ethylene terephthalate) (PET)-based conductive polymer composites were prepared by using these CNT by means of melt mixing with a twin screw extruder. Amount of carboxylic acid groups on the CNT surface increased after acid treatment but decreased with surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 87 publications
0
26
0
Order By: Relevance
“…In addition, the attachment of functional groups on CNTs walls reduces electrical conductivity of the nanocomposites. Several authors reported observation of low composites conductivities because of acid treatment [23][24][25]. They ascribed this performance to the formation of functional groups and defects sites on the surface of the A-MWCNTs after modification process using acid treatment.…”
Section: Electrical Conductivity and Percolation Threshold Valuesmentioning
confidence: 99%
“…In addition, the attachment of functional groups on CNTs walls reduces electrical conductivity of the nanocomposites. Several authors reported observation of low composites conductivities because of acid treatment [23][24][25]. They ascribed this performance to the formation of functional groups and defects sites on the surface of the A-MWCNTs after modification process using acid treatment.…”
Section: Electrical Conductivity and Percolation Threshold Valuesmentioning
confidence: 99%
“…The graphitic sidewalls of the CNTs are not altered, and allow TÍ-TÍ stacking interactions with the adsorbed polymer. The main advantage of this approach is that preserves the intrinsic properties of the CNTs; however, the polymer wrapping decreases the aspect ratio of the reinforcement, and the forces between the CNTs and the polymer are weak, thus the efficiency of the load transfer in the composites might be low [4]. The covalent strategy generally involves nanotubes bound to carboxylic groups in amidation or esterification reactions with amine or hydroxyl groups of polymers or organic molecules [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…c can be calculated using the enthalpies of both crystallization and melting, according to the following equation [27,28]. c of PET and its nanocomposite was calculated from the first-heat run as these data reflect the thermal history of the samples.…”
Section: Crystallization Behaviormentioning
confidence: 99%